Assessment of the frequency of SARS-CoV-2 Omicron variant escape from RNA-dependent RNA polymerase inhibitors and 3C-like protease inhibitors - Takashita, Emi; Fujisaki, Seiichiro; Morita, Hiroko; Nagata, Shiho; Miura, Hideka; Nagashima, Mami; Watanabe, Shinji; Takeda, Makoto; Kawaoka, Yoshihiro; Hasegawa, Hideki (Antiviral research, 2023)
The emergence and spread of antiviral-resistant SARS-CoV-2 is of great concern. In this study, we evaluated the propensity of Omicron variants to escape from RNA-dependent RNA polymerase (RdRP) inhibitors and 3C-like protease (3CLpro) inhibitors. SARS-CoV-2 Delta and Omicron variants were serially passaged in vitro in the presence of RdRP inhibitors (remdesivir and molnupiravir) and 3CLpro inhibitors (nirmatrelvir and lufotrelvir) to detect SARS-CoV-2 escape mutants. After five passages with 3CLpro inhibitors, mutant viruses that escaped from 3CLpro inhibitors emerged; however, in the presence of RdRP inhibitors all variants disappeared within 2–4 passages. Our findings suggest that the frequency of SARS-CoV-2 mutant escape from RdRP inhibitors is lower than that from 3CLpro inhibitors. We also found that Delta variants were more likely to acquire amino acid substitutions associated with resistance to 3CLpro inhibitors under the selective pressure of this drug compared with Omicron variants. •SARS-CoV-2 Delta and Omicron variants were passaged with RdRP inhibitors and 3CLpro inhibitors in vitro.•The frequency of SARS-CoV-2 mutant escape from RdRP inhibitors was lower than that from 3CLpro inhibitors.•Omicron variants acquired substitutions associated with 3CLpro inhibitor-resistance less frequently than Delta variants.